Learning Leadership Strategy in Indonesia during the Covid-19 Pandemic - Teguh Triwiyanto; Asmaa Abusamra; Desi Eri Kusumaningrum; Rana Muhammad Dilshad (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
This study was conducted to know the strategy of learning leadership of the elementary School Headmasters to keep the educational quality during the pandemic of Covid-19.  The three strategies of learning leadership to increase the learning were modeling, monitoring, and professional dialogue.  This research has used qualitative approach.  The study population was 914 elementary school teachers in Kota Batu, province of East Java, Indonesia.  The used sample selection was random sampling, using 76 persons or 8.31 percent of population.  The sampling technic was performed through multistages technic which involving the distribution of population in sub-district groups.  Then, it was seleced ramdomly every sub-district.  The used approach was method of survey.  It has grouped the data using questionnaries and analyzed by technic of analysis of multiple regression.  The study results showed simultaneously that the strategies of modeling, monitoring, and professional dialogue of learning leadership of elementary school headmasters had influences to keep the educational quality during the pandemic of Covid-19. Keywords:  Learning Leadership Strategy, Learning Covid-19 Era, Learning Strategy